Modeling Small Stellar Populations Using Starburst99. Issue Volume 12:Issue S316(2015) (31st March 2017) - Vázquez, Gerardo A.; Leitherer, Claus
Abstract: In this work, we have developed a new approach to form stars from clusters first, where massive stars are formed from fractions of mass of small stellar clusters. This new approximation is based on the empirical power law found in recent years and the maximum stellar mass that can be formed in a cluster. To produce the new models we have used the most recent version of Starburst99 that incorporates the most recent stellar evolution models with rotation. At the verge of solving nearby stellar populations and observing small stellar populations across the universe, this new approach brings a new scope on trying to disentangle the nature of hyper and supermassive stars in small stellar populations. Models for NGC 3603 and NGC 604 are presented. Our most important result is a strong ionizing power from small clusters by forming enough supermassive stars in a cluster of ~ 10 4 M⊙ .